UJI KADAR LEMAK DAN PROTEIN AIR SUSU KAMBING ETAWA DENGAN PEMELIHARAAN SECARA TRADISIONAL - Umbang Arif Rokhayati; Syukri I Gubali; Safriyanto Dako (Gorontalo Journal of Equatorial Animals, 2022)
The Etawa Crossbreed (PE) goat is a cross between an Etawa goat and a peanut goat which has the potential to produce milk. This study aims to determine the fat and protein content of Etawa goat's milk. The type of research used is experimental research with the treatment of taking milk in the morning. This study uses a T test with 3 treatments and 3 replications and the data from the calculation of the Analysis of Variance if it shows a significant difference then is further tested with the BNT and BNJ tests of 5%. Parameters in this study were fat and protein content. The results showed that the fat content of Etawa goat's milk was not significantly different. In the results of statistical analysis, it can be seen that the highest average fat content is at parity 3, which is 7.92%, from parity 2, which is 7.46% and parity 1, which is 6.03%. In the protein content of the highest average, the protein content in parity 2 is 5.46% compared to parity 3 which is 5.03% and parity 1 which is 5.0%. The conclusion is that Etawa goat's milk will have an effect on fat and protein levels, this can be seen at parity 3.